Enhancing the User Experience of Asthma Inhalers: A Redesign Approach - Ishaan Chaudhary; Abdul Kalam (International Journal of Solid State Innovations & Research, 2024)
Asthma is a widespread chronic respiratory condition impacting millions globally, presenting significant challenges in its management and treatment. While conventional inhalers effectively administer medication, they often encounter usability issues, hindering patient adherence and treatment outcomes. This abstract delineates the development and potential impact of a redesigned asthma inhaler aimed at addressing these challenges. Incorporating human-centered design principles, the revamped inhaler prioritizes usability, portability, and effectiveness to enhance the overall management experience. Key features include simplified operation mechanisms, ergonomic design for comfortable handling, and intuitive feedback mechanisms ensuring proper medication delivery. Moreover, the inhaler integrates smart technology for tracking medication usage, providing personalized reminders, and offering real time feedback to users and healthcare providers, thereby fostering greater engagement and proactive management of symptoms. Clinical trials assessing the redesigned inhaler have shown promising outcomes, with improved patient satisfaction, adherence, and treatment efficacy compared to traditional models. Preliminary data also indicate potential reductions in asthma exacerbations and healthcare utilization, underscoring the transformative impact of enhanced inhaler design on overall asthma care. In India, asthma affects approximately 3% of the population, equivalent to around 30 million individuals, with varying prevalence rates among different age groups. In 2014, asthma-related fatalities in India numbered around 57,000, highlighting its significant burden on rural communities. The redesign of the asthma inhaler represents a substantial advancement in respiratory medicine, offering a human-centric approach to asthma management that enhances treatment adherence, efficacy, and overall quality of life for individuals with this chronic condition. Further research and widespread adoption of such innovations hold promise for revolutionizing asthma care and alleviating the global burden of this prevalent respiratory disease.
Keywords: Asthma; human-centric design; inhaler; portability; smart technology